Evaluation of the relative efficacy of copolymerized polylactic-polyglycolic acids alone and in conjunction with polyglactin 910 membrane in the treatment of human periodontal infrabony defects: A clinical and radiological study - Vipin Chhabra (Indian Journal of Dental Research, 2011)
Background: Absorbable synthetic biopolymers have been used as bone filler in Periodontology, proving effective stimulants to bone regeneration. Aim: Copolymerized polylactic and polyglycolic acid is used as a bone filler and polyglactin 910 as a guided tissue regeneration (GTR) membrane to achieve regeneration in periodontal infrabony defects. Materials and Methods: Forty patients with two- or three-walled infrabony defects were selected and randomly divided into two groups. Group A included patients treated with polylactic-polyglycolic acids 50:50 (Fisiograft® ,Ghimsa SPA,Via Fucini, Italy) alone and Group B included patients treated with polylactic-polyglycolic acids (PLA-PGA)50:50 in conjunction with polyglactin acid 910 (Vicryl Mesh® Johnson&Johnson , U.S.A ). Evaluation of clinical parameters probing depth and attachment level and radiographs was done preoperatively and 12 and 24 weeks postoperatively. Results: Both the groups showed statistically significant mean reduction in probing depth and gain in clinical attachment level and linear bone fill. Conclusions: Within the limit of this study, both the treatment modalities are beneficial for the treatment of infrabony defects.